MEMBACA URGENSI MODERASI DALAM MADĪNAH AL-FĀḌILAH AL-FARĀBI: STUDI WACANA PEMBANGUNAN BERKELANJUTAN DI INDONESIA - Nurul Khair; Nuri Barezatul Bilqis; Panji Perdana Putra Priyanto; Sayyida Sayyida; Farid Hamdani (Sekolah Tinggi Agama Islam Sadra, 2022)
This paper is a literature review of Al-Farābi's thoughts on the urgency of the value of moderation in the discourse of sustainable development in Indonesia which is studied through his magnumopus entitled